Right-to-Left Shunting through the Unidirectional Valved Patch after Closure of Ventricular Septal Defect - Talwar, Sachin (Ann Card Anaesth, 2017)
Postoperative transesophageal echocardiography images of a patient undergoing unidirectional valved patch closure of ventricular septal defect in the setting of severe pulmonary hypertension are presented. The images and videos elegantly demonstrate a functioning valve without any obstruction to the left ventricular outflow.